"Green" electrospinning of a collagen/hydroxyapatite composite nanofibrous scaffold. (26th September 2016) - Castilla-Casadiego, David A.; Maldonado, Michael; Sundaram, Paul; Almodovar, Jorge
Abstract: Abstract : In this work, a composite nanofibrous scaffold of collagen/hydroxyapatite was prepared by electrospinning using a mild solvent. Hydroxyapatite particles dispersed into a collagen/acetic acid/water solution was electrospun to yield composite nanofibers. Scanning electron microscopy reveals nanofibers with an average diameter of 342 ± 67 nm, and a rough surface caused by the hydroxyapatite particles. Both X-ray and infrared spectroscopy confirmed the presence of the hydroxyapatite particles embedded in the collagen fibers. The inclusion of hydroxyapatite particles does not alter the native collagen structure. Lastly, these composite nanofibers support pre-osteoblast adhesion. These results show how "green" electrospinning could be used to generate nanocomposite scaffolds with potential biomedical applications.